The Influence Of Consumer Trust And Satisfaction On Customer Loyalty At Sakti Photo Studio Manna Bengkulu Selatan - Aprizal, Aprizal; Hanila , Siti; Rahman , Abdul (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of trust on customer loyalty at Sakti Photo Studio Manna Bengkulu Selatan, to determine the influence of consumer satisfaction on customer loyalty at Sakti Photo Studio Manna Bengkulu Selatan and to determine the influence of consumer trust and satisfaction on customer loyalty at Sakti Photo Studio Manna Bengkulu South. The data collection method in this research is using a questionnaire and the analysis method is multiple linear regression. Based on the research results, it was found that trust has a significant effect on customer loyalty at Sakti Photo Studio Manna, South Bengkulu because the significance value is 0.000 < 0.05. Consumer satisfaction has a significant effect on customer loyalty at Sakti Photo Studio Manna South Bengkulu because the significance value is 0.017 < 0.05. Consumer trust and satisfaction have a significant effect on customer loyalty at Sakti Photo Studio Manna South Bengkulu because the significance value is 0.000 < 0.05.